KEARIFAN LOKAL ARSITEKTURE RUMAH ADAT OSING DALAM PEMBELAJARAN IPS - Fachri Zulfikar (Universitas Negeri Malang, 2020)
This study described the local wisdom of Osing community as reflected on the architecture of traditional houses that could be used as instructional resources for social studies. The approach in this research was qualitative. Data were collected through observation and literature studies of books, journals, papers, written texts, and others related to the local wisdom and social studies education. This study shows that the architecture of the Osing traditional house has specific values that can be used for instructional purpose of social studies education. Students could visit Kemiren village and learn directly from the architerture of the traditional house and other artifacts in the village.